2019
DOI: 10.1002/slct.201900773
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented Tandem Conjugate Addition/C‐O Ester Migration of α‐Cyano Arylacetates with a Quinone Monoimine

Abstract: An unprecedented conjugate addition/CÀ O ester migration of α-cyano arylacetates with a quinone monoamine was presented, which allowed for the synthesis of various 2,2-diarylacetonitriles in moderate to quantitative yields. This method is applicable to a series of α-cyano arylacetates with different aryl groups. Moreover, in order to demonstrate the synthetic utility of this transformation, 2-(cyano(phenyl))-4-(4-methylphenylsulfonamido)ethyl carbonate was subjected in hydrogenation to generate a 2,2-diaryleth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The reactions generated various cyclic imidines in good yield with moderate to good ee values (Scheme 1, a) [6a] . Next we demonstrated an unprecedented tandem conjugate addition/C−O ester migration of ethyl α ‐cyano arylacetates with a quinone monoimine and a kind of novel 2,2‐diarylacetonitriles were obtained in moderate to quantitative yields (Scheme 1, b) [6b] …”
Section: Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…The reactions generated various cyclic imidines in good yield with moderate to good ee values (Scheme 1, a) [6a] . Next we demonstrated an unprecedented tandem conjugate addition/C−O ester migration of ethyl α ‐cyano arylacetates with a quinone monoimine and a kind of novel 2,2‐diarylacetonitriles were obtained in moderate to quantitative yields (Scheme 1, b) [6b] …”
Section: Methodsmentioning
confidence: 89%
“…As an on‐going research on transformations of quinone derivatives and α ‐cyano acetates, herein we used phenyl α ‐cyano‐ α ‐arylacetates in reaction with quinone monoimines. Interestingly, unlike the previous work, [6b] in the presence of catalytic amount of DABCO, the substrates underwent a tandem reaction to generate various 2‐aminobenzofuran derivatives in low to moderate yields (Scheme 1, c).…”
Section: Methodsmentioning
confidence: 91%
“…Zhang et al also developed a divergent reaction between para -quinone monoimines 3 and α-cyano-α-arylacetates 112 . In 2019, they found that tandem conjugate addition and C–O ester migration occurred in refluxing acetonitrile to give various 2,2-diarylacetonitriles in generally good yields (not shown) [ 76 ]. In 2021, they found that an organic base could also promote the [3 + 2] cycloaddition reaction of para -quinone monoimines 3 with α-cyano-α-arylacetates 112 but resulted in the formation of 2-aminobenzofuran 113 , which was protected with di- tert -butyl dicarbonate to give 114 in moderate to good yields ( Scheme 25 ) [ 77 ].…”
Section: Domino Reactions Of Para -Quinone Iminesmentioning
confidence: 99%